PREPARAÇÃO DE NOVOS MATERIAIS À BASE DE COLÁGENO PÍSCEO E QUITOSANA - PENHA, Rosiane Silva (2016)
Chitosan (QT) and collagen (COL) are natural macromolecules of wide interest and application, and which can interact themselves in order to develop blends with biomaterial characteristics. In this work, on account of the fish collagen advantages, we aimed to develop synthesis routes among both biopolymers. It was used chitosan from commercial source, with 82% of deacetylacion degree (DG) determined by conductometric titration, and the collagen was extracted from the swimming bladder and the skin of the Pescada Amarela (Cynosian acoupa) and Gurijuba (Arius luniscutis). The collagen‘s content used on the prepared gels was determined by the 4- hydroxyproline‘s method and equal to 189,24-394,75 mg.g-1. Both materials were separately characterized trough Fourier transform infrared spectroscopy in the infrared (FTIR), X-ray diffraction (XRD), thermal analysis (TGA/DTG and DSC) and scanning electron microscopy (SEM). Amongst the proposed blend‘ synthesis, lyophilization and selective precipitation techniques (saline, alkaline, saline-alkaline) were used in the following QT:COL (wt%) mixtures: 80:20, 50:50 and 20:80. Regarding to precursors, the results of the characterization indicated that the protein structural integrity of the collagen was preserved during extraction and precipitation (FTIR), that it presents an amorphous form (XRD), rough and irregular (SEM). Chitosan also showed amorphous, but with some crystalline domains (XRD), rough (SEM), and thermally stable up to approximately 250 ° C. The obtained materials from chitosan:collagen mixtures and in all different proportions, showed differences in their spectral, thermal and viscosity profiles, indicating interaction between them and suggesting the formation of new materials.